Ice-sheet Dynamics and Postglacial Sedimentary Processes of Coastal Søre Sunnmøre, Southwest Norway - Ossim, Steven Robert (UiT Norges arktiske universitet, 2020)
Submarine glacial landforms have been identified and mapped in order to reconstruct ice sheet dynamics and to describe postglacial sedimentary processes of coastal Søre Sunnmøre in southwestern Norway which lies between 62 and 62.5⁰N. Landform identification has been accomplished through analysis of high-resolution multibeam echosounder (MBES) bathymetric data, backscatter data, LiDAR data, video recordings, and seismic data using ArcGIS (geographical information system). The submarine landscape architecture of coastal Søre Sunnmøre has been largely shaped by glacialinterglacial cycles. The majority of present-day glacial landforms and deposits are a result of growth and decay cycles of the Fennoscandian Ice Sheet during the late Weichselian glaciation of the Pleistocene. A simplified model describing ice sheet dynamics from maximum glacial conditions until final deglaciation is proposed based on evidence including glacial lineations, glacial troughs, morainal banks, and De Geer moraines. Søre Sunnmøre’s dissected and discontinuous distribution of high elevation alpine environments has resulted in a unique glacial dynamics narrative which differs from other localities of southwestern Norway. Sedimentary processes active during final deglaciation up until the present have continued to rework glacially deposited sediment and alter glacial landforms. Fluvial systems and terrestrial mass wasting events continue to supply sediment to marine environments. The occurrence of slope failures, potentially triggered by postglacial isostatic rebound, is indicated by evidence such as submarine rock avalanche deposits and slide scars.